Rheological analysis of ceramic pastes with ethyl cellulose for screen-printing. Issue 4 (May 2015) - Inukai, Koji; Takahashi, Yosuke; Ri, Kinki; Shin, Woosuck
Abstract: Pastes of ceramic particles are used in many industrial applications such as in printed electronic products and solid oxide fuel cells. Ethyl cellulose (EC), a polymer component in the paste, is very useful to control the rheological properties of the pastes for screen printing. In this study, to prepare ceramic La0.6 Sr0.4 Ti0.3 Fe0.7 O3−δ (LSTF) pastes, EC was mixed with an organic solvent, ethylene glycol monobutyl ether acetate, and LSTF powder. The effects of EC and LSTF particle contents were investigated on the rheological properties of the pastes, using shear, stress, frequency-dependence, and a 3-step recovery tests. The recovery ratio of the pastes in the 3-step tests was found to depend strongly on their EC and LSTF particle contents, decreasing at higher contents due to the formation of a strong network. We also investigated the microstructure and surfaces of thick films fabricated through screen-printing, and confirmed that pastes with a low recovery ratio and high viscosity afford smooth surface profiles.